A study on chemical and microbiological properties of kashar cheese produced without using starter culture - Abdullah Badem; Gürkan Uçar (Eurasian Journal of Veterinary Sciences)
Aim: It is aimed to research the change in chemical and microbiological properties of Kashar cheese produced without starter culture during ripening period. Materials and Methods: Fat rate of the raw cow milk was set as 3.0% and was heated to 37˚C and enzyme was added. After coagulum processing, press and fermantation stages, 0.1% of emulsifying salts and 1.5% of salt was added. Cheese was produced through a five-minute melting process at 65˚C. Cheese was packaged by vacuuming and was ripened at 8˚C for 90 days. In samples, dry matter was conducted with gravimetric, fat with Gerber, salt with Mohr and titration acidity with % lactic acidity. pH levels were tested by Nell pH meter. Samples are examined and evaluated statistically from the point of the TAMB, LAB, coagulase (+) S. aureus, coliform bacteria and mould and yeast. Results: Cheeses were ripened at 8˚C for 90 days and analyses were exercised on ripening period. According to results, pH value was found between 5.62-5.76, acidity 0.55-0.83L.a., dry matter 54.93- 58.04%, salt 1.22-1.37%, salt in dry matter 2.21-2.45%, fat 23.67- 25.33% and fat in dry matter 41.20-45.46%. Mean values of the enumeration of TAMB were determined between 5.17-5.75 log cfu/g, LAB 5.49-6.98 log cfu/g, mould-yeast 3.66-4.88 log cfu/g. S. aureus and Coliform group microorganisms were also analyzed, but weren’t detected. In this study samples were assessed and a difference was determined on titratable acidity (P<0.05), but no differences were determined on the others. Conclusion: It may be concluded that Kashar cheese can be produced without using starter culture and can be ripened.